Defining Immunogenic and Radioimmunogenic Tumors - Medler, Terry R.; Blair, Tiffany C.; Crittenden, Marka R.; Gough, Michael J. (Frontiers in Oncology, 2021)
In the cancer literature tumors are inconsistently labelled as ‘immunogenic’, and experimental results are occasionally dismissed since they are only tested in known ‘responsive’ tumor models. The definition of immunogenicity has moved from its classical definition based on the rejection of secondary tumors to a more nebulous definition based on immune infiltrates and response to immunotherapy interventions. This review discusses the basis behind tumor immunogenicity and the variation between tumor models, then moves to discuss how these principles apply to the response to radiation therapy. In this way we can identify radioimmunogenic tumor models that are particularly responsive to immunotherapy only when combined with radiation, and identify the interventions that can convert unresponsive tumors so that they can also respond to these treatments.